Bulk Synthesis and Characterization of Ti3Al Nanoparticles by Flow-Levitation Method. (11th November 2013) - Chen, Shanjun; Chen, Yan; Zhang, Huafeng; Tang, Yongjian; Wei, Jianjun; Sun, Weiguo
Abstract : A novel bulk synthesis method for preparing high pure Ti3 Al nanoparticles was developed by flow-levitation method (FL). The Ti and Al vapours ascending from the high temperature levitated droplet were condensed by cryogenic Ar gas under atmospheric pressure. The morphology, crystalline structure, and chemical composition of Ti3 Al nanoparticles were, respectively, investigated by transmission electron microscopy, X-ray diffraction, and inductively coupled plasma atomic emission spectrometry. The results indicated that the Ti3 Al powders are nearly spherical-shaped, and the particle size ranges from several nanometers to 100 nm in diameter. Measurements of the d-spacing from X-ray (XRD) and electron diffraction studies confirmed that the Ti3 Al nanoparticles have a hexagonal structure. A thin oxidation coating of 2-3 nm in thickness was formed around the particles after exposure to air. Based on the XPS measurements, the surface coating of the Ti3 Al nanoparticles is a mixture of Al2 O3 and TiO2 . The production rate of Ti3 Al nanoparticles was estimated to be about 3 g/h. This method has a great potential in mass production of Ti3 Al nanoparticles.